Closing the access gap for health innovations: an open licensing proposal for universities - Rajkumar Rahul; Chokshi Dave A; Chaifetz Samantha; Scales David; Benkler Yochai (BMC, 2007)
Abstract Background This article centers around a proposal outlining how research universities could leverage their intellectual property to help close the access gap for health innovations in poor countries. A recent deal between Emory University, Gilead Sciences, and Royalty Pharma is used as an example to illustrate how 'equitable access licensing' could be put into practice. Discussion While the crisis of access to medicines in poor countries has multiple determinants, intellectual property protection leading to high prices is well-established as one critical element of the access gap. Given the current international political climate, systemic, government-driven reform of intellectual property protection seems unlikely in the near term. Therefore, we propose that public sector institutions, universities chief among them, adopt a modest intervention - an Equitable Access License (EAL) - that works within existing trade-law and drug-development paradigms in order to proactively circumvent both national and international obstacles to generic medicine production. Our proposal has three key features: (1) it is prospective in scope, (2) it facilitates unfettered generic competition in poor countries, and (3) it centers around universities and their role in the biomedical research enterprise. Two characteristics make universities ideal agents of the type of open licensing proposal described. First, universities, because they are upstream in the development pipeline, are likely to hold rights to the key components of a wide variety of end products. Second, universities acting collectively have a strong negotiating position with respect to other players in the biomedical research arena. Finally, counterarguments are anticipated and addressed and conclusions are drawn based on how application of the Equitable Access License would have changed the effects of the licensing deal between Emory and Gilead.